Analisis Level Risiko Bahaya Pada Usaha Pencucian Mobil dengan Metode AS/NZS 4360:2004 - Deny Poniman Kosasih; A. Moeslihat Komara; Hari Din Nugraha; Cecep As Sidik (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2020)
Over time, the number of motorized vehicles has increased significantly, this is in line with the need for vehicle maintenance, namely vehicle washing, especially cars. But on the other hand, there is a risk of danger that occurs in the car wash process. This study aims to identify potential hazards in the work process at a car wash. The type of survey research, the method of the assessment process refers to the Australian/New Zealand standard (AS/NZS 4360:2004). The results showed the highest level of risk in the car washing process at Car Wash "X" which was in stage 4, namely cleaning under the car and stage 1 parking the car with the Very High category. Stage 5 cleans the engine and stage 3 cleans the car body in the Substantial category. Stage 2 releases the car in the Priority 3 category. And the lowest level of risk is at stage 6, namely Finishing in the Acceptable category. Recommendations that can be given to Car Wash business actors are workers must use Personal Protective Equipment (PPE) in the form of boots, gloves when washing to avoid chemical liquids that cause skin irritation. In addition, the placement of the car washer is placed parallel to the worker so that when turning on the machine it is easy and ergonomic. In addition, in the construction of the floor to be designed with a rougher roughness so as not to slip easily due to a wet floor.